Applying the Principles of Good Corporate Governance in Corporate Financial Management - Hasanudin Hasanudin (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
This study aims to analyze the application of the principles of Good Corporate Governance (GCG) in corporate financial management. The method used in this research is descriptive qualitative research. The results of the research GCG principles that are applied are transparency, accountability, independence, and corporate social responsibility which have an impact on company management where 1) the principle of transparency refers to the openness and clarity of information provided by the company to stakeholders, 2) The principle of accountability emphasizes the importance company to be responsible for policies and actions taken in managing company finances, 3) The principle of responsibility emphasizes the importance of companies to pay attention to the interests of all stakeholders in making decisions and policies, 4) The principle of independence emphasizes the importance of companies to avoid conflicts of interest and maintain independence in decision making decisions, and 5) the principle of fairness emphasizes the importance of fair and equal treatment of all company stakeholders. The implication of this research is that companies must apply GCG principles in their financial management to achieve long-term success.